Knowledge, Attitude, and Practice Related to Eating Behavior for the Prevention of Type 2 Diabetes Among High School Students - Kusumawati, Nila; Glorie, Kim; Hamid, Abdul (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Aims: Diabetes mellitus is a major global public health concern, particularly in Indonesia. Eating behavior, particularly type 2 diabetes mellitus (T2DM), plays a crucial role in the prevention of diabetes. This study aimed to assess high school students’ knowledge of T2DM, attitudes toward healthy eating, and dietary practices related to diabetes prevention, as well as to examine the correlations among these variables. Methods: The study was conducted from May to October 2024 in three sub-districts of Kampar Regency, Riau Province, Indonesia. A total of 207 high school students were recruited through convenience sampling. Data were collected using a validated knowledge, attitude, and practice (KAP) questionnaire comprising four sections: Sociodemographic characteristics, Knowledge about T2DM, Attitudes toward healthy eating, and Dietary practices. Univariate analysis was conducted to describe the distribution of KAP levels, and Spearman’s rank-order correlation was used to examine the relationships among KAP scores. Results: Most senior high school students (80.2%) demonstrated a moderate overall KAP level. Specifically, 49.3% had moderate knowledge of T2DM, 81.2% exhibited a neutral attitude toward healthy eating, and 59.9% reported moderate dietary practices. Spearman’s rank correlation analysis revealed a weak but statistically significant positive correlation between knowledge and attitude (p=0.145, p=0.037), and between knowledge and practice (p=0.137, p=0.048). A moderate-to-strong positive correlation was found between attitude and practice (p=0.530), indicating a stronger association between these two variables. Conclusion: The findings indicate that students’ knowledge of T2DM is positively associated with both their attitudes toward healthy eating and their dietary practices, although the strength of these correlations is weak. In contrast, a moderate to strong positive correlation was observed between attitude and practice, suggesting that students with more positive attitudes toward healthy eating were more likely to engage in desirable dietary behaviors.